Development of Tissue Integrity indicators to advance the quality of spinal cord injury rehabilitation: SCI-High Project. (30th September 2019) - Flett, Heather; Wiest, Matheus J.; Mushahwar, Vivian; Ho, Chester; Hsieh, Jane; Farahani, Farnoosh; Alavinia, S. Mohammad; Omidvar, Maryam; Houghton, Pamela E.; Craven, B. Catharine
Abstract : Objective: To establish structure, process and outcome indicators to evaluate tissue integrity in Canadians with spinal cord injury or disease (SCI/D) in the first 18 months following inpatient rehabilitation admission. Method: A Working Group comprised of Canadian subject matter experts in the Domain of Tissue Integrity was formed to define the construct of tissue integrity. A literature review was conducted and a Driver diagram produced to identify factors that influence tissue integrity in individuals with SCI/D. Facilitated meetings were conducted to identify and achieve consensus on structure, process and outcome indicators. Rapid cycle testing was used to pilot test proposed indicators for face validity and feasibility within a quality improvement context. Results: The structure indicators are the proportion of patients with SCI/D who have access to a mirror for skin checks and the proportion of patients who have access to patient education on tissue integrity; the process indicator is the proportion of patients who completed daily head-to-toe skin checks; the intermediary outcome indicator is pressure injury (PI) incidence during inpatient rehabilitation; and the final outcome indicator is the proportion of individuals with intact skin at 18 months following rehabilitation admission. Conclusion: The set of indicators established for the Domain of Tissue Integrity are specifically focused on aspects of care that can impact the maintenance of tissue integrity and the prevention of PI and align with current practice guidelines. The implementation and evaluation of these indicators nationally have the potential to improve care for Canadians with SCI/D.